Barriers and facilitators for implementing programmes and services to address hyperglycaemia in pregnancy in low and middle income countries: A systematic review. (November 2018) - Kragelund Nielsen, Karoline; Damm, Peter; Bygbjerg, Ib. C.; Kapur, Anil
Abstract: Aims: An estimated 87.6% of hyperglycaemia in pregnancy cases are in low and middle income countries (LMICs). The aim of this study is to review the evidence on barriers and facilitators to programmes and services addressing hyperglycaemia in pregnancy in LMICs. Methods: A systematic review and narrative synthesis was conducted based on searches in PubMed. A total of 23 qualitative and quantitative studies were included. Results: Barriers and facilitators exist at the health system level, individual level and social and societal levels and are often interacting. At the health system level they relate to capacity in terms of human and material resources; availability of feasible and appropriate guidelines; organisational management and referral pathways. Individual level barriers and facilitators include knowledge; risk perception; illness beliefs; financial condition; work obligations; concerns for the baby and hardship associated with services. At the social and societal level important factors are: perceptions and norms related to women's roles, mobility and health; the knowledge and support of women's social network; and structural aspects. Conclusions: Numerous factors influence programmes and services addressing hyperglycaemia in pregnancy in LMICs. Thus, several components are needed to ensure detection, treatment and follow-up of women with hyperglycaemia in pregnancy.